A Catalytic Nanoreactor Based on in Vivo Encapsulation of Multiple Enzymes in an Engineered Protein Nanocompartment. (14th September 2016) - Giessen, Tobias W.; Silver, Pamela A.
Abstract: Bacterial protein compartments concentrate and sequester enzymes, thereby regulating biochemical reactions. Here, we generated a new functional nanocompartment in Escherichia coli by engineering the MS2 phage capsid protein to encapsulate multiple cargo proteins. Sequestration of multiple proteins in MS2‐based capsids was achieved by SpyTag/SpyCatcher protein fusions that covalently crosslinked with the interior surface of the capsid. Further, the functional two‐enzyme indigo biosynthetic pathway could be targeted to the engineered capsids, leading to a 60 % increase in indigo production in vivo. The enzyme‐loaded particles could be purified in their active form and showed enhanced long‐term stability in vitro (about 95 % activity after seven days) compared with free enzymes (about 5 % activity after seven days). In summary, this engineered in vivo encapsulation system provides a simple and versatile way for generating highly stable multi‐enzyme nanoreactors for in vivo and in vitro applications. Abstract : Engineering enzyme encapsulation : Engineering the MS2 phage capsid results in modified nanocages that can be specifically loaded with multiple enzymes. The two‐enzyme indigo biosynthetic pathway was targeted to the engineered compartment and shown to increase indigo production in vivo. Particles could also be isolated in their active form and showed enhanced long‐term in vitro stability.